The Effectiveness of Hybrid Working In Improving Employee Work-Life Balance and Employee Performance - Setiyono, Ahmad; Fahmilia Rahmita; Muhammad Fuzail (Al Tijarah, 2024)
Technological advances have changed the traditional work paradigm into a more flexible model, especially the Hybrid Working work model, which combines working from the office (WFO) and working from home (WFH). This model has gained popularity during the COVID-19 pandemic as companies try to adapt to the new reality. This study investigates the impact of hybrid working on work-life balance. The goal is to understand how this work model can improve employee Work-Life Balance. The research methodology used is a library research method, which involves collecting and analysing relevant academic sources, including journals, articles and publications related to Hybrid Working, work-life balance and employee performance. Research design involves thorough selection, screening, and analysis of literature to gain meaningful insights. Findings show that Hybrid Working significantly improves work-life balance, leading to increased productivity and employee performance. Key aspects include improved time management, reduced stress, and increased commitment to the organization. This model allows employees to fulfil personal responsibilities while maintaining work efficiency. Companies or organizations that adopt hybrid working are expected to increase employee productivity, welfare and loyalty, reducing overall turnover rates. Effective implementation depends on leveraging technology, strong leadership, and supportive policies. Keywords: Hybrid working, Work life balance, Employee performance